Dispositional and situational factors at work: A validation of scales and examination of effects on job satisfaction - Pujol-Cols, Lucas J. (2019)
Purpose: The purpose of this paper is to examine the psychometric properties of the Spanish version of the Core Self-Evaluations Scale (CSES) and the Brief Index of Affective Job Satisfaction (BIAJS) in terms of internal consistency and factor structure and to, subsequently, analyze the influence of a set of dispositional factors (namely, core self-evaluations, CSEs) and situational factors (namely, psychosocial factors) on job satisfaction. Design/methodology/approach: In total, 209 academics from an Argentinian university completed online surveys at two stages, separated in time, to reduce the common method bias. Findings: The Spanish version of the CSES and the BIAJS showed acceptable psychometric properties, which were similar to those previously reported in North-American, European and Asian settings. Hierarchical regression analyses revealed that both situational and dispositional factors are significant predictors of job satisfaction. Research limitations/implications: The CSES and the BIAJS seem to be valid and reliable instruments for assessing CSEs and job satisfaction, respectively, in Latin America. The adoption of an interactionist approach that includes both situational and dispositional factors is crucial in future research examining job satisfaction. Practical implications: Managers should carefully evaluate the personality traits of candidates during personnel selection, as well as the working conditions they offer to their employees, since both factors seem to affect job satisfaction. Originality/value: This paper contributes to the validation of two scales that may promote future organizational behavior/psychology research in Latin America. In addition, it provides empirical evidence on the relative influence of a set of situational and dispositional factors on job satisfaction, thus contributing to the resolution of the person-situation debate.